Design of Web-based Report Card Processing Information System at MTS Negeri 4 Kebumen - Mukhamad Hasim Iswanto (Jurnal Indonesia Sosial Teknologi, 2024)
Based on observations made, the processing of report card scores in MTs N 4 Kebumen is currently still manual, so a lot of time and energy is needed to carry out the task. In addition, the distribution of report cards is also still conventional because parents must come to school to take them, for this reason, a report card application is needed that can improve services to students quickly in terms of distributing report card scores while making it easier for teachers to fill in report cards. The purpose of this study is to design a web-based value processing application. In designing this application, the author uses the stages of SDLC development with the Waterfall process model. The design of this web-based report card processing information system can improve the quality of report card processing in MTs N 4 Kebumen. The programming language that the author uses is PHP and uses a MySQL database. To test the feasibility of the system, the authors used blak bock testing. The final result of this research is the creation of a web-based MTs N 4 Kebumen report card application.